Pakistan Power Position under the influence of China-Pakistan Economic Corridor: An Analysis of Economic and Strategic Opportunities - Fatima, Sahar; Amna, Mehar; Saeed, Hina (Annals of Human and Social Sciences, 2024)
This research paper wants to create the effects of CPEC on the Pakistan Power Position. Geographic location of Pakistan plays a particular role in its power ambition. The strategic and Economic benefits of Pakistan is connected with China. Pakistan is bordered by China which is the world’s second largest economy wants to reach in Gulf states, and toward the European and African markets. CPEC is the eminent project of the Belt and Road initiative which gives the shortest way to China in the Gulf region. In this paper, the data is collected by using qualitative method through content analysis. This multi-billion project has the potential to effect Pakistan’s national power elements. Pakistan being 6th largest populous country is capable of gaining major investment through CPEC. Geographic location of Pakistan is crucial in bringing economic stability as well as opportunities. Pakistan has to take appropriate measures for catching this project.